Directed Evolution of an Improved Aminoacyl‐tRNA Synthetase for Incorporation of L‐3, 4‐Dihydroxyphenylalanine (L‐DOPA). Issue 27 (24th May 2021) - Thyer, Ross; d'Oelsnitz, Simon; Blevins, Molly S.; Klein, Dustin R.; Brodbelt, Jennifer S.; Ellington, Andrew D.
Abstract: The catechol group of 3, 4‐dihydroxyphenylalanine (L‐DOPA) derived from L‐tyrosine oxidation is a key post‐translational modification (PTM) in many protein biomaterials and has potential as a bioorthogonal handle for precision protein conjugation applications such as antibody–drug conjugates. Despite this potential, indiscriminate enzymatic modification of exposed tyrosine residues or complete replacement of tyrosine using auxotrophic hosts remains the preferred method of introducing the catechol moiety into proteins, which precludes many protein engineering applications. We have developed new orthogonal translation machinery to site‐specifically incorporate L‐DOPA into recombinant proteins and a new fluorescent biosensor to selectively monitor L‐DOPA incorporation in vivo. We show simultaneous biosynthesis and incorporation of L‐DOPA and apply this translation machinery to engineer a novel metalloprotein containing a DOPA‐Fe chromophore. Abstract : Catechols are capable of diverse interactions with metals, radical chemistry, the ability to form redox‐mediated crosslinks, and play an important role in many biological polymers. Genetic tools are presented that enable site‐specific incorporation of the catechol amino acid 3, 4‐dihydroxyphenylalanine (L‐DOPA) into proteins in bacteria, and a new DOPA‐specific fluorescent biosensor for monitoring incorporation in living cells.